Spontaneous emission noise resilience of coupled nanolasers - Roos, Aycke; Meinecke, Stefan; Lüdge, Kathy (Frontiers in Photonics, 2023)
We investigate the spontaneous emission noise resilience of the phase-locked operation of two delay-coupled nanolasers. The system is modelled by semi-classical Maxwell-Bloch rate-equations with stochastic Langevin-type noise sources. Our results reveal that a polarization dephasing time of two to three times the cavity photon lifetime maximizes the systems ability to remain phase-locked in the presence of noise induced perturbations. The Langevin noise term is caused by spontaneous emission processes which change both the intensity auto-correlation properties of the solitary lasers and the coupled system. In an experimental setup these quantities are measurable and can be directly compared to our numerical data. The strong parameter dependence of the noise tolerance that we find may show possible routes for the design of robust on-chip integrated networks of nanolasers.